2006
DOI: 10.1111/j.1478-4408.2006.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoyellowing of wool. Part 1: Factors affecting photoyellowing and experimental techniques

Abstract: The yellowing of wool exposed to sunlight is a serious commercial shortcoming compared to cotton and synthetic fibres, particularly when photostable brilliant whites and bright pastel shades are required. Part 1 of this review discusses the effects of light on wool keratin and the factors that affect the rate of photoyellowing, including oxidative bleaching, fluorescent whitening and the presence of moisture. The effect of variation of the wavelength of light, particularly attenuation of the ultraviolet wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 103 publications
0
71
0
1
Order By: Relevance
“…17 Emission of PICL from polymers is dependent on the presence of oxygen, and for hydrocarbon polymers the accepted dominant mechanism involves a bimolecular reaction between two adjacent polymer macroperoxy radicals via an excited carbonyl intermediate, as shown by eq 6 in Scheme 1.…”
Section: Picl Decay Profiles and Preliminary Kinetic Analysismentioning
confidence: 99%
“…17 Emission of PICL from polymers is dependent on the presence of oxygen, and for hydrocarbon polymers the accepted dominant mechanism involves a bimolecular reaction between two adjacent polymer macroperoxy radicals via an excited carbonyl intermediate, as shown by eq 6 in Scheme 1.…”
Section: Picl Decay Profiles and Preliminary Kinetic Analysismentioning
confidence: 99%
“…This reaction is catalyzed by trace metals such as iron and copper (150,151). It has been proposed that the photoyellowing mechanism for wool may involve a free-radical chain reaction involving formation of hydroperoxide intermediates (via the Bolland and Gee autooxidation mechanism (152) as is the case for most other polymers), rather than a singlet oxygen mechanism (149,(153)(154)(155). Studies using electron spin resonance (156,157) and chemilumninescence techniques (158) have shown that free radicals are formed when wool is exposed to UV light.…”
Section: Yellowingmentioning
confidence: 99%
“…Trace metal ions (such as Fe) enhance the photodegradation process of several fibers, including cotton. For instance, they participate to the oxidative degradation of cellulose [20,21] and increase the concentration of hydroxyl radical generated upon light exposure [18]. As well, iron influences the degradation of cellulose in iron gall-ink manuscripts [22].…”
Section: Prussian Blue and Textile Substrate Act As A Redox Systemmentioning
confidence: 99%